Analisis kandungan organoklorin pada area akuakultur di Perairan Pulau Nain - Pratasik, Gerald A.; Tumembouw, Sipriana S.; Kusen, Diane J.; Undap, Suzanne L.; Ngangi, Edwin L. A.; Kreckhoff, Reni L. (e-Journal BUDIDAYA PERAIRAN, 2024)
Organochlorine pesticides are one type of pesticide that is often used and some organochlorine pesticides are included in the group of Persistent Organic Pollutants, this type of pesticide is a pollutant that is a problem because it is resistant and bioaccumulative. Organochlorine characteristics that can adversely affect the environment are; 1). Decomposes very long in soil, air, water, and in living things, and can also stay in the environment for a long time. 2). It can enter the food chain and accumulate in fat tissue, making it difficult to dissolve in water. 3). Can be carried far through air and water. Seeing the nature of organochlorine pesticides that can last a long time in the environment and can be carried away by air and water, and the discovery of organochlorines in Manado Bay does not rule out the possibility that organochlorine pesticides can also exist in the waters of Nain Island. The objectives of this study are: (1) Measuring the physical parameters of water chemistry (temperature, DO, pH, and salinity) and organochlorine pesticide levels in Nain Island waters, (2) Analyzing organochlorine levels in Nain Island seawater samples. Measurements and sampling were carried out on Nain Island, Wori District, North Minahasa Regency on May 22, 2023. The results showed that there were organochlorines of endrin and DDT types in the waters of Nain Island, the concentration of endrin and DDT did not exceed the threshold of seawater quality standards PP RI No. 22 of 2021. The results of measuring water quality parameters show that the measurement location is still under seawater quality standards. Keywords: pesticides, water quality, aquaculture, seaweeds